Hibridni oscilator za analogne in digitalne prizemeljske televizijske oddajnike - Kosi, Andrej (Informacije MIDEM, 2007)
Currently, the transitien or preparation for the changeover from analog television to digital television is in progress. Consequences of this transitien are modifications that will have to occur in the distribution, transmission and recepti on of television signals. This article will mainly focus on television transmitters, or more precisely to their oscillator. The demands for oscillators used in digital television are different from those used in analog television and for this reason, simple modification of the latter is not possible. The major differences are in the small est frequency step and phase noise demand. The smallest frequency step for digital television is 1 Hz, which is far less than the few kHz step required for analog television. The phase noise requirement is specified in the standard for DVB-T (Digital Video Broadcasting - Terrestrial) and is al so higher than that for analog television. This article will present the hybrid oscillator, which is suitable for use in both analog and digital transmitters. The term hybrid oscillator refers to an oscillator that combines two or more different technologies together. In this case, the hybrid oscillator combines direct digital synthesizer (DDS) and phase locked loop (PLL). The advantages and disadvantages of DDS and PLL are shortly presented. DDS output is limited with frequency range, frequency spurs and harmonics. On the other hand, DDS has a fast settling time and a very fine frequency step ( Hz). PLL can be used for higher frequencies with a wider frequency range, however it is hard to achieve a small frequency step, low phase noise and fast settling time at the same time. This is because the improvement ofone parameter degrades the others. For our hybrid oscillator, DDS is used as a source for the reference frequency of the PLL. In so doing, fine frequency step is achieved and the wanted phase noise is preserved. For best results it is very important to use high quality electronic paris that contribute little to phase noise degradation. On the basis of conclusions, we have made a prototype of this hybrid oscillator for UHF (Ultra High Frequency) frequency band. In addition, a number of different measurements of the hybrid oscillator were taken to confirm theoretical calculations and expectations. The final measurement results have shown that the hybrid oscillator is suitable for use in both analog and digital television transmitter.
Keywords: analogni signali; digitalni signali; televizijska tehnika